Pancasila as an Paradigm Sustainable Development Goals - Ahmad Dion Ghojaji Ahmad Dion Ghojaji; Nikur Adiratna Sari Gulo; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Abstract - Basically, the MGDs and SDGs have in common and have the same goals, namely, the SDGs continue the MDGs' ideals which want to concentrate on tackling hunger and poverty in the world. However, the document agreed upon by world leaders in 2000 expired in 2005, world leaders feel that the Millennium Development Goals agenda needs to be continued, so that it is superior to a proposed document for the Sustainable Development Goals. Different from the previous Millennium Development Goals (MDGs), the SDGs are designed to involve the entire development sector, be it the Government, Civil Society Organizations (CSOs), the private sector, academia, and so on. Approximately 8.5 million citizens' voices around the world also contribute to the SDGs Goals and Targets. The Sustainable Development Goals (SDGs) are global action plans agreed by world leaders, including Indonesia. To eliminate poverty, reduce inequality and protect the environment. For Indonesia, the goal of sustainable development is to make Indonesia a developed country, able to develop in all aspects, and to be able to properly and comprehensively apply and implement the concept of a sustainable economy, so that Indonesia can become a fully developed country. The goals of the SDGs are global values ​​and are basically the roots of the values ​​of Pancasila. Adherence to the principles of the sustainable development goals of the Pancasila economic system illustrates this. The Pancasila economic system or people's economy is guided by the values ​​of Pancasila. This is in accordance with the 1945 Constitution and Pancasila. In order for the plan for the Sustainable Development Goals to be successful, the role of the government must prioritize current policies and improve social justice and human rights, of course, must be guided by the values ​​of Pancasila and the 1945 Constitution to realize the Indonesian nation. Keywords: Millenium development goals, pancasila, sustainable development goals,